Analisis Koefisien Debit Bangunan Ukur Daerah Irigasi Kalibawang - Ratih, Silvia Yulita; Prandono, Tri; Putra, Khoiru Badri Misbakhu (Universitas Kristen Maranatha, 2025)
. Based on the field observation at discharge measuring buildings, sometimes there are differences in the results of the distribution of discharge on land that is irrigated with the discharge channeled by officers. From this phenomenon, it is necessary to check whether there are any irregularities in the discharge measuring building. This research aims to calibrate the discharge measuring building in Kalibawang primary canal. The existing type of measuring building is a wide threshold measuring building. The principle of discharge measurement is to measure flow velocity, wet cross-sectional area, and depth. The measurement of the flow velocity in the channel using a calibrated current meter at various variations in door opening height. The current meter was chosen because it has good accuracy for measuring flow velocity. The data from this research was collected by dividing the channel width into several piece at various water depths, wet cross-sectional widths, and flow speeds. From the analysis results, there are differences between the theoretical discharge and the measured discharge. For example, the discharge formula coefficient for the first location is 1.67 b.h1.5, the formula correction is 1.78 b.h1.5. The positive or negative deviations from the comparison results between theoretical discharge and measurement discharge are caused by differences in the results of measurements on the current meter. The cause of this difference is damage to the body of the measuring building, such as cavities or holes and sedimentation